Effectiveness of the Pfizer-BioNTech (BNT162b2) vaccine against the omicron variant of SARS-CoV-2 among adults aged 50 and above: A case-control study in Lebanon, June 2022 - Maryo Baakliny; Nada Ghosn; Nadine Saleh; Patrick Maison (PLoS ONE, 2025)
The emergence of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the subsequent coronavirus disease 2019 (COVID-19) pandemic with the continuous evolution of the virus into variants such as Alpha, Beta, Delta, Omicron and others necessitates an on-going surveillance and evaluation of vaccine effectiveness (VE).This study focuses on assessing the real-world performance of the Pfizer-BioNTech (BNT162b2) vaccine against the Omicron variant. This study employs a test-negative, case-control design, a methodology commonly utilized for estimating the VE in influenza studies. It evaluates SARS-CoV-2 test results in individuals aged 50 and older who had influenza-like illness (ILI) or COVID-like illness (CLI) symptoms and presented to the sentinel sites, classifying positive cases as “cases” and negative as “controls.” Data collection was done through a standardized questionnaire administered by the Epidemiological Surveillance Unit (ESU) COVID-19 team via phone interviews. Logistic regression analysis was performed to measure the association, taking into account all confounding factors. The results indicate a 14% VE against contracting the disease among fully vaccinated individuals. Factors such as age and underlying conditions significantly influenced VE. The findings of this study highlight the effectiveness of the Pfizer-BioNTech (BNT162b2) vaccine in reducing the odds of symptomatic COVID-19, particularly by decreasing the prevalence of key symptoms such as fever, cough, myalgia, and loss of taste or smell. Breakthrough infections still occurred, indicating that while the vaccine reduces symptom severity, it may not fully prevent infection This VE is lower compared to previous variants, indicating potential challenges in vaccine efficacy. The study underscores the need for an on-going monitoring and potential booster doses to enhance protection, especially against evolving variants like Omicron.